Automated air ventilation / Muhammad Danish Hakim Zaharun - Zaharun, Muhammad Danish Hakim (2023)
The weather at this time is getting hotter by the day. Poor quality air flow will cause various diseases that harm our health. Therefore, automated air ventilation was created to improve air flow in closed places so that good air flow can enter and can remove poor quality air from automated air ventilation. The objective emphasized in the project is that I can design automated air ventilation by using suitable materials such as motors, sensors, aluminum profiles and so on. In addition, I will also analyze the quantity and critical parts that are in the automated air ventilation. Aluminum profile is cut into pieces arranged according to the size that fits the closed room. The motor and sensor are also installed on automated air ventilation to make it easier for users. I expect that the automated air ventilation can work well and provide benefits to users